Margaret Chase Smith Library 2017 High School Essay Contest: Crusade against the Drugs, Not the Users - Kyes, Gabrielle (Maine Policy Review, 2017)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The essay prompt for 2017 was, How would you address the current lethal drug epidemic? The essays have been edited for length.
Keywords: drug users; opioid addiction